Modeling the impact of GCI components on Ukraine competitiveness - Дзвоник, Р. Я.; Горбаль, Н. І.; Гошовська, О. В.; Dzvonyk, R. Ya.; Horbal, N. I.; Hoshovska, O. V. (Видавництво Львівської політехніки, 2020)
Глобальна конкуренція зростає не лише на рівні продуктів/фірм, а й серед країн. Конкурентоспроможність країн визначається багатьма факторами та оцінюється за різними підходами та методами. Одними із найвідоміших є методології Інституту розвитку менеджменту (IMD) та Всесвітнього економічного форуму (WEF). Індекс глобальної конкурентоспроможності ВЕФ ґрунтується на 12 групах із понад 100 показників. Остання версія (GCI 4.0) охоплює: 1. Сприятливе середовище (інституції; інфраструктура; прийняття ІКТ; макроекономічна стабільність). 2. Людський капітал (здоров’я; навички). 3. Ринки (товарний ринок; ринок праці; фінансова система; розмір ринку). 4. Інноваційна екосистема (динамічність бізнесу; інноваційні можливості). За даними GCI 2019, Україна на 85-му місці із 141 країни. Конкурентоспроможність України погіршується вже третій рік поспіль. Основний регрес відбувся у сферах: фінансової системи, охорони здоров’я, упровадження ІКТ, макроекономічної стабільності та інноваційних можливостей. На основі цих 12 компонентів розроблено багатофакторну регресійну модель їх впливу на конкурентоспроможність України на основі агрегованих і стандартизованих показників GCI 2009–2019 рр. Для оцінювання параметрів моделі використано метод найменших квадратів і додаток “Аналіз даних” програми MS EXCELL. Отриману модель протестовано. У результаті моделювання виявлено, що на конкурентоспроможність України найбільше вплинули показники інституцій та розвитку фінансового ринку. Отже, вони повинні стати пріоритетними напрямами розвитку та політики держави.

Global competition is growing not only on a products/firms level, but also among countries. There are many approaches to interpretation of a concept of the “country competitiveness”, which in particular means “the state of the country in the global market due to the international division of labor, national conditions and factors of production and its ability to compete effectively in world markets”. The competitiveness of countries is determined by many factors and is assessed by different approaches and methods. Some of the best known are the methodologies of the Institute for Management Development (IMD) and the World Economic Forum (WEF). Potential investors are guided by them when making decisions about investing in the economy, financial institutions – when evaluating countries as recipients of capital, etc. The WEF’s Global Competitiveness Index (GCI) is based on 12 groups of over 100 indicators and is regularly adjusted to meet current challenges facing national economies. The latest version – GCI 4.0 – includes: 1. Enabling Environment (1.1. Institutions. 1.2. Infrastructure. 1.3. ICT adoption. 1.4. Macroeconomic stability). 2. Human Capital (2.1. Health. 2.2. Skills). 3. Markets (3.1. Product market. 3.2. Labour market. 3.3. Financial system. 3.4. Market size). 4. Innovation Ecosystem (4.1. Business dynamism. 4.2. Innovation capability). According to GCI 2019, the top five are: Singapore, the United States, Hong Kong, Netherlands and Switzerland, while Ukraine – in the 85th place out of 141 countries. The competitiveness of Ukraine has been deteriorating for the third year in a row. The main regression is in the spheres of: financial systems, healthcare, ICT implementation, macroeconomic stability and innovation opportunities. Considering those 12 components, the multifactorial regression model for Ukraine competitiveness was designed based on aggregated and standardized GCI indicators of 2009–2017 and 2018–2019. To estimate the parameters of the multifactor regression model, the least squares method and the application “Data Analysis” of the program MS EXCELL were used. The obtained model has been tested. As a result of modeling, it can be seen that – institutions indicator and – indicator of financial market development had the greatest influence on the competitiveness of Ukraine. Thus, they should become the priority areas of the state development and policy
Моделювання впливу складових GCI на конкурентоспроможність України
Keywords: конкурентоспроможність; Індекс глобальної конкурентоспроможності; моделювання; кореляційно-регресійний аналіз; багатофакторна модель; competitiveness; Global competitiveness index; modeling; correlationregression analysis; multifactor model; C1; C82; E69; F01; F69; O57; P47; 330.1 005 (477)